2017
DOI: 10.1089/chi.2016.0255
|View full text |Cite
|
Sign up to set email alerts
|

Obese Adolescents Show Reduced Cognitive Processing Speed Compared with Healthy Weight Peers

Abstract: Obese adolescents show slower cognitive processing speed while maintaining equivalent performance on executive functioning compared with their healthy weight peers. The group differences in the anterior portion of the CC, responsible for frontal lobe interhemispheric communication, may in part explain our processing speed findings. Future studies should include a longitudinal design and diffusion tensor imaging to examine the integrity of white matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 40 publications
1
29
0
2
Order By: Relevance
“…Different methods are appropriate for specific cognitive functions, which may explain the lack of agreement among studies. Many of the test items that comprise standardized tests of academic performance are impacted by processing speed and rapid decision making; processes known to be negatively related to obesity (88).…”
Section: Outcome Assessmentsmentioning
confidence: 99%
“…Different methods are appropriate for specific cognitive functions, which may explain the lack of agreement among studies. Many of the test items that comprise standardized tests of academic performance are impacted by processing speed and rapid decision making; processes known to be negatively related to obesity (88).…”
Section: Outcome Assessmentsmentioning
confidence: 99%
“…Executive function encompasses the cognitive processes that allow regulation of behavior toward a goal, self-monitoring, problem solving, complex attention, and decision-making [34]. Obesity is associated with decreased executive function performance including deficits in attention, abstract reasoning, and organization skills necessary for successful memory and visuo-constructional performance [6,13,35]. A metaanalysis of 20 studies by Veronese et al [10] showed that weight loss in obese people is associated with improvement across various cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the studies in T1DM patients, most studies suggest that T2DM subjects experience cognitive decline. T2DM most often is associated with deficits in cognitive domains, declarative memory, attention and executive function, alterations also seen in children and adolescents with Metabolic Syndrome or obesity and glycaemic disorders [45,46]. The GC, the disease duration and cerebrovascular complications are considered risk factors that influence the magnitude of the cognitive decline [12].…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…According to the authors, the domains marked by asterisks have strong supporting data[34].Additionally, Sweat et al, in a study carried out in 162 adolescents (aged 19.53 ± 1.53 years), found that obese adolescents showed slower processing speed maintaining equivalent executive functioning compared with their healthy siblings[46]. Whereas, a recent systematic review performed Barkin et al, showed a consistent inverse association between obesity and executive function in children and adolescents, emphasising that in future research is necessary to use a standardised method of executive function measurement in order to establish causality with obesity and develop new and more effective intervention strategies[47].…”
mentioning
confidence: 91%